Complete the equation \( \begin{array}{r}9 \frac{1}{3} \quad 8+\frac{3}{3}+\frac{1}{3} \\ -3 \frac{2}{3}-3 \frac{2}{3}\end{array} \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To complete the equation, we first convert the mixed numbers into improper fractions and perform the calculations. The first term, \(9 \frac{1}{3}\), can be converted as follows: \[ 9 \frac{1}{3} = \frac{28}{3} \] Now let's add the second part of the equation: \[ 8 + \frac{3}{3} + \frac{1}{3} = 8 + 1 + \frac{1}{3} = 9 + \frac{1}{3} = \frac{28}{3} + \frac{1}{3} = \frac{29}{3} \] Now we calculate the entire first part: \[ \frac{28}{3} + \frac{29}{3} = \frac{57}{3} \] Next, we compute the second part: Both terms, \( -3 \frac{2}{3} \), convert to: \[ -3 \frac{2}{3} = -\frac{11}{3} \] So, \[ -\frac{11}{3} - \frac{11}{3} = -\frac{22}{3} \] Now we put it all together: \[ \frac{57}{3} - \frac{22}{3} = \frac{57 - 22}{3} = \frac{35}{3} \] Thus, the completed equation results in: \[ \frac{35}{3} \] or \(11 \frac{2}{3}\).